Effort-reward imbalance and health outcomes in emergency nurses: the mediating role of work–family conflict and intrinsic effort - Le Tong; Le Tong; Ling Zhu; Ling Zhu; Hao Zhang; Hao Zhang; Luying Zhong; Luying Zhong; Dongmei Diao; Dongmei Diao; Xiaoli Chen; Xiaoli Chen; et al. (Frontiers in Public Health)
BackgroundEmergency nurses experience high stress, but the mechanisms linking effort-reward imbalance to health outcomes are unclear. Work–family conflict might mediate this relationship, and intrinsic effort could moderate it. This study aimed to explore these interactions and their impact on nurse health.MethodsA prospective cross-sectional survey was conducted from 30 tertiary hospitals across 19 provinces in mainland China. Participants completed validated scales to measure effort-reward imbalance, work–family conflict, somatic symptoms, and mental health symptoms. Statistical analyses, including mediation and moderation, were performed using the PROCESS macro to evaluate the relationships between the variables.ResultsIn this study, 1,540 emergency nurses were finally included. The analysis revealed that 80.5% of participants reported experiencing effort-reward imbalance, which was significantly associated with increased somatic symptoms and mental symptoms. Work–family conflict was identified as a significant mediator in the relationship between effort-reward imbalance and health outcomes, with a direct effect of effort-reward imbalance on overall symptoms (β = 0.554, p < 0.001). Additionally, intrinsic effort moderated the impact of effort-reward imbalance on work–family conflict; moderate levels of emotional investment provided protection against burnout, while excessive intrinsic effort heightened the risk of mental health deterioration (β = −0.104, p < 0.001).ConclusionThese findings underscored the urgent need for targeted interventions that address both effort-reward imbalance and work–family conflict in healthcare settings. Enhancing workplace conditions and supporting emotional engagement among emergency nurses are essential strategies for improving their well-being and reducing burnout risk. Future research should focus on longitudinal studies to assess the effectiveness of these interventions over time.